APPLICATION OF SIR MODEL TO ANALYZE THE SPREADING OF COVID-19 - NUR BALQIS KHALISSA KAMAROZAMAN; NORZURIA IBRAHIM (Enhanced Knowledge in Sciences and Technology, 2022)
Covid-19 disease situation has been worrying people around the world because it has caused many deaths and spread easily through the respiratory droplets. This research aims to analyze the stability of SIR model for spreading of Covid-19 using Maple and to develop the simulation of SIR model using Excel besides comparing the data of Covid-19 between 2020 and 2021. This study focused on analyzing the spreading of Covid-19 in Malaysia by applying the SIR model to real data. The data spreading of Covid-19 in Malaysia have been used in this study were started in the interval between 18 March 2020 until 31 October 2021. In addition, in this research, the stability analysis was carried out with two equilibrium points which includes the disease-free equilibrium point and endemic equilibrium point using Maple software. It was to study the dynamics behavior of Covid-19 epidemic by generating a simulation of phase portrait for susceptible (S) versus infected (I) where the results will be showed that the spreading increased in certain time. Lastly, the SIR model was verified in applying the model to real data of spreading Covid-19 to analyze its trend and compared the data between 2020 and 2021 graphically.